Efficacy and safety of pharmacological treatment of psoriatic arthritis: a systematic literature research informing the 2023 update of the EULAR recommendations for the management of psoriatic arthritis - Kerschbaumer, Andreas (2024)
Objectives: To obtain an overview of recent evidence on efficacy and safety of pharmacological treatments in psoriatic arthritis (PsA). Methods: This systematic literature research (SLR) investigated the efficacy and safety of conventional synthetic (cs), biological (b) and targeted synthetic (ts) disease-modifying antirheumatic drugs (DMARDs) in patients with PsA. A systematic database search using Medline, EMBASE, Cochrane CENTRAL was conducted to identify relevant articles published since the previous update in 2019 until 28 December 2022. Efficacy was assessed in trials while for safety observational data were also considered. Adverse events of special interest were infections (including herpes zoster, influenza and tuberculosis), malignancies, major adverse cardiovascular events, venous thromboembolisms, liver disease, laboratory changes and psychiatric adverse events. No meta-analyses were performed. Results: For efficacy, of 3946 articles screened, 38 articles (30 trials) were analysed. The compounds investigated included csDMARDs (leflunomide, methotrexate), bDMARDs inhibiting IL17 (bimekizumab, brodalumab, ixekizumab, izokibep, secukinumab,), IL-23 (guselkumab, risankizumab, tildrakizumab), IL-12/23 (ustekinumab) as well as TNF (adalimumab, certolizumab-pegol, etanercept, infliximab, golimumab) and Janus Kinase inhibitors (JAKi) (brepocitinib, deucravacitinib, tofacitinib, upadacitinib). The compounds investigated were efficacious in improving signs and symptoms of PsA, improving physical functioning and quality of life. For safety, 2055 abstracts were screened, and 24 articles analysed: 15 observational studies and 9 long-term follow-ups of trials, assessing glucocorticoids, TNFi, IL-17i, JAKi, IL-12/23i and PDE4i (apremilast). Safety indicators were generally coherent with the previous SLR in 2019. Conclusion: The results of this SLR informed the task force responsible for the 2023 update of the European Alliance of Associations for Rheumatology recommendations for pharmacological management of PsA.